THE SUPERVISION IN THE PROCESS OF INVESTIGATION AND INVESTIGATION OF CORRUPTION (POLICE AND PROSECUTION) - Fence Wantu; Lusiana Margareth Tijow; Nasruddin Yusuf (Jurnal Ilmiah Al-Syir'ah, 2020)
The investigation process is an integral part of the investigation. Put merely, and the research is an essential part of the study. The emphasis of investigations is on finding and gathering evidence so that the criminal act found becomes apparent and can find the culprit. In principle, the analysis of a criminal case is a continuation of the research carried out previously. For an event that has been declared a criminal act by the investigator, the next step is to investigate who the perpetrator of the crime is. This research was conducted by examining field data. This writing is to provide an ideal concept of supervision in the process of suspected criminal acts and then goes to the supervision of the investigation process. The investigation is carried out by officials appointed by Law as referred to in applicable laws and regulations. Still, management needs to be carried out by all parties, including the community. This management is a fundamental affirmation that all stakeholders play a significant role in eradicating corruption that threatens society's stability and security and weakens the institutions and values of democracy and justice, endangers sustainable development and law enforcement.